Petrography and Structural Studies of Rocks of Kufai and Environs, Kaltungo Inlier of Hawal Massif, Northeastern Nigeria - Ibrahim Bute, Saleh; Asma’u Hardo, Usman; Musa Bappah Usman; Mukkafa, Shehu; Olasehinde Adeyinka; Auwalu Dalha, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
The crystalline basement rocks of Kaltungo inlier is composed mainly of granitic rocks which were later ruptured by volcanic rocks. We employed petrographical and structural studies with the aim to preliminary classify the rock suites, their relationship and structures of Kufai and environs. The granite suites comprised of porphyritic biotite granite and equigranular granites; they both show similar mineralogy that comprised of quartz (~55 vol. %), K-feldspar (~25 vol. %), plagioclase (~10 vol. %), biotite (~10 vol. %). The volcanic suites comprised of trachyte and basalt, the basalt is made up of plagioclase (~37 vol. %), olivine (~20 vol. %), augite (~10 vol. 5%) and Fe-oxides (28 vol. %) while the trachyte is composed of K-feldspar (~70 vol. %), plagioclase ((~10 vol. %), biotite (~10 vol. %) and quartz (~10 vol. %). The structures observed are joints and quartzo-felsdpathic veins. The veins show a dominant trend of NE-SW while the joints show a dominant trend of NW-SE; this is consistent with the major NE-SW lineaments of the Pan-African basement. The gradational contact between the porphyritic biotite granite and equigranular granite indicates they are coeval, and the sharp contacts between the granitic and volcanic suggest a later event. Based on the mineralogical and structural features of the studied rock, the granite suites is part of the Pan-African basement whereas the volcanic rocks are likely part of Tertiary volcanics of northeastern Nigeria.